Pengaruh Manipulasi Aktivitas Riil melalui Komponen Arus Kas Kegiatan Operasi terhadap Kinerja Pasar - Sitti Zulaeha (-)
This study aims to provide empirical evidence regarding : ( 1 ) the effect of the manipulation of real activities through cash flow component of operating activities on the performance of the market, ( 2 ) companies that have a higher market performance tends to manipulate real activities, ( 3 ) the effect on the performance of real activities manipulation market . The object of research is a services company listed on the Stock Exchange during the five years (2008-2012 ) as many as 64 services companies. The sampling technique used was purposive sampling. Data were analyzed using SPSS 19.0 for windows which consist of three types of analysis, path analysis, simple regression, and analysis of the different test t - test.The results of this study indicate that the manipulation of real activities through cash flow component operations negatively affect the performance of the market, it is proved that not all companies are trying to show high profits in the financial statements that the company 's financial performance looks good. There are several companies which in fact have a high income, there are also companies that intentionally reveal higher profits but in reality lower profits. Earnings growth continues to increase from year to year, giving a positive signal about the future prospects of the company, because the profit is one measure of the performance of the company. Companies that have a higher market performance tends to manipulate real activities through cash flow component of operating activities, it is proved that the company that has the ability to increase earnings, its share price will tend to rise. The results of the analysis of the different test conducted also showed that statistically there is a difference company doing real activities manipulation and companies that do not do a real activity.